2016
DOI: 10.1097/mph.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the FGFR4 Gene Is Associated With Risk of Neuroblastoma and Altered Receptor Degradation

Abstract: Background Outcomes for children with high-risk neuroblastoma are poor, and improved understanding of the mechanisms underlying pathogenesis, recurrence and treatment resistance will lead to improved outcomes. Aberrant growth factor receptor expression and receptor tyrosine kinase signaling are associated with the pathogenesis of many malignancies. A germline polymorphism in the FGFR4 gene is associated with increased receptor expression and activity and with decreased survival, treatment resistance, and aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…After full review, 91 articles were excluded for the following reasons: 1) they were review articles or meta-analyses, 2) they did not investigate association between the FGFR4 rs351855 G>A polymorphism and cancer risk, 3) they were not case-control studies, or 4) had no enough data reported to calculate the odds ratios (ORs) and 95% confidence intervals (CIs). One article was further excluded because of the departure from Hardy–Weinberg equilibrium (HWE) [ 32 ]. Only 23 articles consisting of 27 individual studies investigated the association between the FGFR4 rs351855 G>A polymorphism and cancer risk, and fit the eligibility criteria (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After full review, 91 articles were excluded for the following reasons: 1) they were review articles or meta-analyses, 2) they did not investigate association between the FGFR4 rs351855 G>A polymorphism and cancer risk, 3) they were not case-control studies, or 4) had no enough data reported to calculate the odds ratios (ORs) and 95% confidence intervals (CIs). One article was further excluded because of the departure from Hardy–Weinberg equilibrium (HWE) [ 32 ]. Only 23 articles consisting of 27 individual studies investigated the association between the FGFR4 rs351855 G>A polymorphism and cancer risk, and fit the eligibility criteria (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have also identified additional germline genetic variants in neuroblastoma patients, including single-nucleotide polymorphisms in LIN28B, BARD1, and LMO1, among others [26][27][28][29] as well as other polymorphisms in other chromosomal regions yet to be fully characterized [30,31]. These polymorphisms occur relatively frequently in the general population and may contribute to the development of sporadic neuroblastoma, although the functional roles of these germline variants and other somatic alterations remain to be elucidated.…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%
“…A common nonsynonymous single nucleotide polymorphism (SNP) at codon 388 (rs351855 G>A) in exon 9, which results in a change of glycine to arginine (Gly 388 Arg), was recognized in the transmembrane domain of the EGFR4 receptor [ 13 ]. Several studies inspected the relationship between FGFR4 gene rs351855 G>A polymorphism and numerous types of cancer including breast cancer [ 13–18 ], cervical cancer [ 19–21 ], colon cancer [ 13 , 18 , 22 ], gastric cancer [ 23 ], prostate cancer [ 24–27 ], head and neck squamous cell carcinoma (HNSCC) [ 28 , 29 ], oral squamous cell carcinoma (OSCC) [ 30 , 31 ], lung cancer [ 32–34 ], hepatocellular carcinoma [ 35–37 ], sarcoma [ 38 ], skin cancer [ 39 ], neuroblastoma [ 40 ], non-Hodgkin’s lymphoma [ 41 ], and glioma [ 42 ]. There are few direct reports about the effect of FGFR4 polymorphism on the gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…FGFR4 rs351855 polymorphism induced higher expression of FGFR4 protein and worse prognosis in breast cancer [ 43 ]. It has been reported that the rate of degradation of the Arg 388 receptor was slower than the Gly 388 receptor in neuroblastoma cells and also initiated internalization of the receptor into multivesicular structures (Rev1-1) [ 40 ]. In another investigation, the researchers showed that expression of the FGFR4 Arg 388 protein activated the extracellular signal-related kinase pathway with subsequent expression of several genes which were associated with the aggressive form of prostate cancer [ 44 ], (Rev1-1).…”
Section: Introductionmentioning
confidence: 99%